Pendekatan Etnosains Pada Pembelajaran IPA Dalam Proses Pembuatan Bekasam Untuk Menumbuhkan Nilai Kearifan Lokal - Anggi Desviana Siregar (Institut Agama Islam Negeri Kerinci, 2021)
This study examines the knowledge of the people of Manggul-Lahat Village, South Sumatra about the making of bekasam and compares or correlates it with scientific concepts. This research uses descriptive qualitative research method with an etnoscience approach. The steps taken in collecting data are interviews, observation, documentation and literature study. The results of this study indicate that bekasam is a typical food of the people in Indonesia, especially the people of South Sumatera, Kalimantan and Central Java whose management knowledge is passed down from generation to generation. Furthermore, in the manufacturing process there is a scientific study relationship between culture and science. Thus, the process of making bekasam can be used as a natural science learning material. Therefore, the role of the teacher is very important in order to convey the values ​​of local wisdom with science.